2015
DOI: 10.1002/jwmg.867
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean diversity of the continental shelf and slope off southern australia

Abstract: We recorded a diverse cetacean assemblage from systematic aerial surveys in productive upwelling waters off southern Australia in 2002-2013. Surveys recorded 133 sightings of 15 identified cetacean species consisting of 7 mysticete (baleen) whale species, 8 odontocete (toothed) species, and 384 sightings of unidentified dolphins. This is the first assessment of cetacean diversity for the region and we found diversity to be comparable with other productive regions elsewhere. Differential spatial and temporal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
(48 reference statements)
0
8
1
Order By: Relevance
“…g . aerial vs ship-based surveys), species richness (n≥21) was similar to other productive areas worldwide such as the temperate waters of southern Australia (n≥15, [ 4 ]) and the California current system (n = 21, [ 44 ]), the tropical waters of Gulf of Mexico (n = 28, [ 6 ]), the eastern Pacific (n = 30, [ 45 ]) and the cold waters in the Pacific sub-Arctic gyres (n = 24, [ 46 ]). The fact that 90% of the species richness was recorded within the first four cruises indicates that the area was properly surveyed.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…g . aerial vs ship-based surveys), species richness (n≥21) was similar to other productive areas worldwide such as the temperate waters of southern Australia (n≥15, [ 4 ]) and the California current system (n = 21, [ 44 ]), the tropical waters of Gulf of Mexico (n = 28, [ 6 ]), the eastern Pacific (n = 30, [ 45 ]) and the cold waters in the Pacific sub-Arctic gyres (n = 24, [ 46 ]). The fact that 90% of the species richness was recorded within the first four cruises indicates that the area was properly surveyed.…”
Section: Discussionmentioning
confidence: 63%
“…Oceanic productive areas are known to aggregate high species richness and abundance of top predators, such as cetaceans, and are usually situated near hydrographic fronts and abrupt topographies which are characterized by strong sea surface temperature gradients and high chlorophyll concentrations [ 1 , 2 , 3 ]. In southern Australia, for example, the most common cetacean species were associated to upwelling season and migration cycles [ 4 ]. In the oceanic waters of Gulf of Mexico species appeared to concentrate near the slope or around eddies, where the amount of potential prey for cetaceans may be consistently greater in some seasons [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of marine mammal species are known to take advantage of this convergence, which is associated with areas of high primary productivity. Sightings surveys off the coast of south Australia have detected several beaked whales (Gill et al, 2015) with one particular sighting involving a single group of 20 unidentified mesoplodonts largely fitting the description of Gray's beaked whales (P. Gill, pers. comm.).…”
Section: Discussionmentioning
confidence: 70%
“…Other than observational effort, the oceanographic characteristics of an area are often attributed to the differences observed in cetacean distribution and diversity [44, 45]. In this study the OTW region demonstrated the highest diversity and the highest stranding rate of cetaceans along the open ocean coastal regions.…”
Section: Discussionmentioning
confidence: 73%